The influence of video games in acquiring English (English proficiency) / Azyyati Che Daud - Che Daud, Azyyati (Faculty of Education, 2014)
This study was carried out to investigate the influence of video games in enhancing English proficiency level of second language speakers in Malaysia. The English language aspects under the investigation were divided into 5 categories,namely vocabulary, grammar, listening, speaking and reading skill. Besides that, the research was to find out the factors affecting learners' demotivation in playing video games. The study was carried out in UiTM Seksyen 17, Shah Alam in 2014,with 26 respondents from the Faculty of Education. The data gathered from the research has been analysed and tabulated accordingly. Based on the findings, this study has achieved the objectives, thus proving the main hypothesis which was video games do influence English proficiency. Through the outcomes gained,future studies can be done to gain deeper understanding on the issue.